2004
DOI: 10.1093/jac/dkh174
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of allicin, the reactive molecule of garlic, in inhibiting Aspergillus spp. in vitro, and in a murine model of disseminated aspergillosis

Abstract: These favourable results, despite the short half-life of this compound in vivo, support further studies of controlled sustained release or more prolonged administration of allicin as a treatment for aspergillosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
64
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 16 publications
5
64
2
1
Order By: Relevance
“…The bioactive property of garlic was formed by the interaction of the non-protein amino acid alliin and the enzyme alliinase [22]. Thiosulfinates were produced through interaction, most commonly induced by crushing the mature garlic clove, of which around 70% of the bioactive compounds produced was allicin (diallylthiosulphinate) [22,23]. Allicin was responsible for garlic's pungent odour and the many medicinal health benefits associated with the consumption of garlic [24].…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive property of garlic was formed by the interaction of the non-protein amino acid alliin and the enzyme alliinase [22]. Thiosulfinates were produced through interaction, most commonly induced by crushing the mature garlic clove, of which around 70% of the bioactive compounds produced was allicin (diallylthiosulphinate) [22,23]. Allicin was responsible for garlic's pungent odour and the many medicinal health benefits associated with the consumption of garlic [24].…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme and substrate are located in different compartments of the clove, so that allicin is generated only when the clove is crushed (18,41). Many lines of evidence indicate that allicin is primarily responsible for garlic's antiinfective properties (1,5,15,34,38,43), although studies have also found that ajoene, a metabolite of allicin found when garlic is crushed specifically in oil, also has some antibacterial properties (27). In fact, one study found that ajoene has an inhibitory effect on the erythrocytic stages of Plasmodium (30).…”
mentioning
confidence: 99%
“…Allicin (diallyl-dithiosulfinate), the biologically active molecule of garlic, has been shown to have a very wide range of antimicrobial activities and contributes to the defense of the garlic plant against soil microorganisms (1,11,15,20,29,36,44). Allicin is produced by the catalytic reaction of the enzyme alliinase (EC 4.4.1.4) with the inert, nonprotein amino acid substrate alliin [(ϩ)-S-allyl-cysteine sulfoxide].…”
mentioning
confidence: 99%
“…Crushing the garlic clove breaks down the compartmentalization and brings the enzyme and its substrate into contact, leading to allicin production (20,30). The potential use of pure allicin as an anti-Aspergillus agent in vivo was shown in our previous work (44). Despite its short half-life, five repetitive doses of pure allicin administered intravenously (i.v.)…”
mentioning
confidence: 99%
See 1 more Smart Citation